2014
DOI: 10.1158/0008-5472.can-14-0431
|View full text |Cite
|
Sign up to set email alerts
|

Common Genetic Variants in NEFL Influence Gene Expression and Neuroblastoma Risk

Abstract: The genetic etiology of sporadic neuroblastoma is still largely obscure. In a genome-wide association study, we identified single nucleotide polymorphisms (SNP) associated with neuroblastoma at the LINC00340, BARD1, LMO1, DUSP12, HSD17B12, HACE1 and LIN28B gene loci, but these explain only a small fraction of neuroblastoma heritability. Other neuroblastoma susceptibility genes are likely hidden among signals discarded by the multiple testing corrections. In this study, we evaluated 8 additional genes selected … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
80
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 80 publications
(81 citation statements)
references
References 46 publications
1
80
0
Order By: Relevance
“…[89] This original GWAS has been expanded and replicated as additional patient samples have been accrued, leading to the identification of DNA alleles significantly associated with high-risk and low-risk neuroblastoma predisposition, including CASC15, BARD1, LMO1, LIN28B, HACE1, DUSP12, DDX4, IL31RA, HSD17B12, NEFL, TP53, AND NBPF23 (Table 1). [72, 74, 75, 79, 81, 88, 89, 102104, 107] The discovery of these susceptibility loci demonstrates the utility of interrogating GWAS signals for clues into the underlying biology driving neuroblastoma genesis.…”
Section: Genetic Susceptibility To Sporadic Neuroblastomamentioning
confidence: 99%
See 1 more Smart Citation
“…[89] This original GWAS has been expanded and replicated as additional patient samples have been accrued, leading to the identification of DNA alleles significantly associated with high-risk and low-risk neuroblastoma predisposition, including CASC15, BARD1, LMO1, LIN28B, HACE1, DUSP12, DDX4, IL31RA, HSD17B12, NEFL, TP53, AND NBPF23 (Table 1). [72, 74, 75, 79, 81, 88, 89, 102104, 107] The discovery of these susceptibility loci demonstrates the utility of interrogating GWAS signals for clues into the underlying biology driving neuroblastoma genesis.…”
Section: Genetic Susceptibility To Sporadic Neuroblastomamentioning
confidence: 99%
“…[102] Overexpression of NEFL in cells with a protective allele caused cells to adopt a more differentiated phenotype and to have reduced proliferative capacity. The authors suggested that decreased expression of NEFL alters the differentiation state of sympathetic neurons and may predispose neuroblastoma.…”
Section: Genetic Susceptibility To Sporadic Neuroblastomamentioning
confidence: 99%
“…In particular, consistent with a putative effect of the variant T-allele on weakening the mRNA secondary structure, we did show that miR-204 is able, by means of a still undisclosed mechanism, to decrease the stability of the PHOX2B mRNA, at a larger extent in the presence of the T allele than in the presence of the A allele. This suggests a putative role of SNP rs1063611 as susceptibility locus for neuroblastoma, thus making highly probable an association between this SNP and neuroblastoma which might deserve to be tested in a large case-control study [38,39]. Our result also suggests a genotype-dependent effect of miR-204 which should be therefore considered when reasoning about possible therapeutic interventions and personalized medicine.…”
Section: Accepted Manuscriptmentioning
confidence: 57%
“…Several gene polymorphisms are significantly associated with the risk of neuroblastoma, such as LIN28B [10], HACE1 [10], BARD1 [11], LMO1 [12], HSD17B12 [13], DDX4 [13], IL31RA [13], and DUSP12 [13], which have been discovered by means of GWAS. Besides, several genes, such as FAS [14], FASL [14], NEFL [15], and TGFBR3L [16], have been discovered by candidate gene approach.…”
Section: Introductionmentioning
confidence: 99%